2013
DOI: 10.5812/cardiovascmed.10719
|View full text |Cite
|
Sign up to set email alerts
|

Deep sedation in patients undergoing atrioventricular nodal reentry tachycardia ablation

Abstract: Background:General anesthesia and deep sedation can be used during cardiac EPS to relief pain and provide comfort and immobility, but many electrophysiologists avoid sedation for better arrhythmia induction.Objective:To determine anesthesia effects in ablation procedures in adults, we used intravenous anesthetic agents in patients who underwent slow pathway ablation.Patients and Methods:One hundred patients who were to undergo radiofrequency catheter ablation were randomly assigned to with and without intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16] Even under conditions of deep sedation or general anesthesia, isoproterenol is effective for arrhythmia induction. 17 However, as noted in prior publications, 18 a dramatic price increase in March 2015 19 resulted in the wholesale acquisition cost of isoproterenol increasing from $26.20 to $1,790.11 per milligram. The nonspecific alpha-and beta-adrenergic stimulant, epinephrine (priced at $14.96 per milligram), is an alternative to isoproterenol.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16] Even under conditions of deep sedation or general anesthesia, isoproterenol is effective for arrhythmia induction. 17 However, as noted in prior publications, 18 a dramatic price increase in March 2015 19 resulted in the wholesale acquisition cost of isoproterenol increasing from $26.20 to $1,790.11 per milligram. The nonspecific alpha-and beta-adrenergic stimulant, epinephrine (priced at $14.96 per milligram), is an alternative to isoproterenol.…”
Section: Introductionmentioning
confidence: 92%
“…To date, the largest series of cases involving tilt table testing, EPS and supraventricular tachycardia (SVT) ablation, and premature ventricular contraction ablation have all used isoproterenol as the primary provocative drug . Even under conditions of deep sedation or general anesthesia, isoproterenol is effective for arrhythmia induction . However, as noted in prior publications, a dramatic price increase in March 2015 resulted in the wholesale acquisition cost of isoproterenol increasing from $26.20 to $1,790.11 per milligram.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 In our study, the combination of dexmedetomidine and propofol enabled us to achieve both preserved inducibility and a safe procedure without complications related to deep sedation. 19 Utility of propofol in catheter ablation for AVNRT has been described in the past, 24,26 but we evaluated the inducibility and the outcome not only for AVNRT but also for other types of PSVT, and under deep sedation with ASV instead of minimal sedation.…”
Section: Induction During Deep Sedationmentioning
confidence: 99%
“…Therefore, major studies have indicated the application of sonographic guided cannulation for central venous catheterization ( 14 ). Some evidence-based studies suggested good clinical outcomes for central venous catheterization for vascular access in neonates, infants and for arterial catheterization.…”
mentioning
confidence: 99%